Global resuscitation alliance utstein recommendations for developing emergency care systems to improve cardiac arrest survival. (November 2018) - Nadarajan, G.D.; Tiah, L.; Ho, A.F.W.; Azazh, A.; Castren, M.K.; Chong, S.L.; El Sayed, M.J.; Hara, T.; Leong, B.S.; Lippert, F.K.; Ma, M.H.M.; Ng, Y.Y.; et al.
Abstract: Introduction: The Global Resuscitation Alliance (GRA) was established in 2015 to improve survival for Out- of-Hospital Cardiac Arrest (OHCA) using the best practices developed by the Seattle Resuscitation Academy. However, these 10 programs were recommended in the context of developed Emergency Care Systems (ECS). Implementing these programs can be challenging for ECS at earlier stages of development. We aimed to explore barriers faced by developing ECS and to establish pre-requisites needed. We also developed a framework by which developing ECS may use to build their emergency response capability. Method: A consensus meeting was held in Singapore on 1st–2nd August 2017. The 74 participants were key stakeholders from 26 countries, including Emergency Medical Services (EMS) directors, physicians and academics, and two Physicians who sit on the World Health Organisation (WHO) panel for development of Emergency Care Systems. Five discussion groups examined the chain of survival: community, dispatch, ambulance and hospital; a separate group considered perinatal resuscitation. Discussion points were voted upon to reach a consensus. Results: The answers and discussion points from each groupwere classified into a table adapted from WHO's framework of development for Emergency Services. After which, it was used to construct the modified survival framework with the chain of survival as the backbone. Eleven key statements were then derived to describe the pre-requisites for achieving the GRA 10 programs. The participants eventually voted on the importance and feasibility of these 11 statements as well as the GRA 10 programs using a matrix that is used by organisations to prioritise their action steps. Conclusion: In this paper, we propose a modified framework of survival for developing ECS systems. There are barriers for developing ECS systems to improve OHCA survival rates. These barriers may be overcome by systematic prioritisation and cost-effective innovative solutions.